Hubungan Tingkat Pengetahuan dengan Perilaku Pencegahan Covid-19 di Wilayah Kerja UPT Puskesmas Jekan Raya pada Tahun 2022: The Relationship of Knowledge Level with Behavior Prevention Covid-19 in the Work Area of the Jekan Raya Puskesmas in 2022 - Deni Kurniawan; Rizki Muji Lestari; Dita Wasthu Prasida (Jurnal Surya Medika (JSM), 2023)
The world is shocked by the emergence of a new type of virus, a virus known as the corona virus. Coronaviruses (CoV) are part of a family of viruses that cause illness ranging from the flu to the more severe illness of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). such as Middle East Respiratory Syndrome (MERS-CoV). At the Jekan Raya Health Center there were 121 cases with 2 deaths and 113 cases recovered. Therefore, prevention of this disease. This study aims to determine the level of the relationship between knowledge and COVID-19 prevention behavior in the community at the Jekan Raya Public Health Center, Palangka Raya City. The design of this study used an analytic survey, this research was conducted at the Jekan Raya Health Center in Palangka Raya City on July 22, 2022. The population of this study was all people who visited the Jekan Raya Health Center in Palangka Raya City. City with a sample of 65 people. The test in this study is a sampling technique using purposive sampling. The results showed that the respondents' knowledge of Covid-19 prevention was mostly in the good category 56 (86.1%). The Chi-Square test of respondents' knowledge and behavior shows p value = 0.000 a < 0.01 from the data results, it can be concluded that there is a relationship between respondents' knowledge and COVID-19 prevention behavior in the community.